2021
DOI: 10.3389/fmed.2021.794561
|View full text |Cite
|
Sign up to set email alerts
|

New Applications of HBOC-201: A 25-Year Review of the Literature

Abstract: If not cured promptly, tissue ischemia and hypoxia can cause serious consequences or even threaten the life of the patient. Hemoglobin-based oxygen carrier-201 (HBOC-201), bovine hemoglobin polymerized by glutaraldehyde and stored in a modified Ringer's lactic acid solution, has been investigated as a blood substitute for clinical use. HBOC-201 was approved in South Africa in 2001 to treat patients with low hemoglobin (Hb) levels when red blood cells (RBCs) are contraindicated, rejected, or unavailable. By pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 113 publications
0
16
1
Order By: Relevance
“…Free serum hemoglobin was previously described as having adverse effects on kidneys, with extravasated hemoglobin causing nephrotoxicity and scavenging of nitric oxide (NO), thus leading to hypertension and higher intrarenal resistance [ 25 , 26 ]. The latter could also be observed in the HBOC groups in our study, while a possible obstruction of glomeruli could not be shown upon histological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Free serum hemoglobin was previously described as having adverse effects on kidneys, with extravasated hemoglobin causing nephrotoxicity and scavenging of nitric oxide (NO), thus leading to hypertension and higher intrarenal resistance [ 25 , 26 ]. The latter could also be observed in the HBOC groups in our study, while a possible obstruction of glomeruli could not be shown upon histological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…36 Despite the failure of the HBOC products tested in the early 2000s, the search for a safe and efficacious HBOC is continuing today, 7,37 and newer applications are also being proposed. 3,8 Blood is a rare national resource. Its safety and availability are of vital concern.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Eight different hemoglobin preparations were developed and subjected to rigorous testing by commercial companies and the US Army, culminating in phase III clinical trials in which the safety and the ability of the product to effectively replace transfusion was tested. 8 Unfortunately, all the tested products failed to achieve FDA licensure because of both safety and efficacy concerns. 7,9 The reasons for the failure of the products are varied and may involve flaws in the products and in the execution of the trials.…”
Section: Background: Why Hboc's?mentioning
confidence: 99%
“…Safety and efficacy of HBOCs was explored using numerous preclinical and clinical studies and a HBOCs product, HBOC-201 is approved for surgical patients with acute anemia and has been available in South Africa since 2001 [134]. However, a metaanalysis of cell-free hemoglobin-based blood substitutes concluded that the use of HBOCs was associated with a significantly increased risk of death and myocardial infarction based on an analysis of the available data from 13 randomized controlled trials [135]. After that the USFDA suspended all HBOC trials in the United States.…”
Section: Regulation Of Blood Pressure After Hemorrhagic Shockmentioning
confidence: 99%
“…After that the USFDA suspended all HBOC trials in the United States. Nonetheless, it was argued that if the risk of death due to low hemoglobin outweighed the risk of HBOCs, suspension on all HBOC trials could be fatal for these patients [135]. Subsequently, clinical trials for HBOCs are made available only through expanded access to save patients' lives when other interventions are not available.…”
Section: Regulation Of Blood Pressure After Hemorrhagic Shockmentioning
confidence: 99%